Mobilization for new rights and legal change: The campaign for the Maria de Penha law - Alves Maciel, Débora; Brito Prata, Paula da Silva (Política. Revista de Ciencia Política, 2011)
Based on a political process approach, the article analyses an episode of legal mobilization which took place between 2003 and 2006 during the campaign in favour of the Maria da Penha Law in Brazil. Promoted by feminist organizations, the national movement resulted in new legal tools against domestic violence and violence against women: The Maria da Penha Law. It is argued that the emergence and success of the legal campaign depended on a set of factors, including the national and international political opportunity structure of the 1990’s, the style of the activist’s careers, the reframing of violence against women, and new strategies for legal and political mobilization.